If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(1) + 2 = 0 Multiply -6 * 1 -6 + 2 = 0 Combine like terms: -6 + 2 = -4 -4 = 0 Solving -4 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6=-2x+64 | | -6(2)+2= | | AD/BC/AC/BD | | (1/(3x)-(2/(4x)=(3/4) | | 150=15r | | u+3.9=6.13 | | 18.99x=30 | | 2x-25+x+5=180 | | (xy-1)(xy+1)(x+3)=0 | | 3=7+b | | -6(-1)+2= | | (8)(15)(5)(9)= | | 12.99x=30 | | 6-3x=4x+9 | | a-15=-19 | | (1/3x)-(2/4x)=(3/4) | | 5x^3=130 | | 3(2x-2)=10+x | | (4x-12)+52=90 | | -6(0)+2= | | 3(4x+5)-5(7x-7)=2(6x+1) | | 0=x^2-9x-8 | | -(x+11)=2(2x-6) | | 5*(1/3)-(-2/3)X | | 2(6x-1)=120 | | -30=-14+v | | 4x=4(0+2x) | | 6x+68=9x-7 | | 2x+20+3x+8=180 | | -3=x-15 | | 9sin^2x+2=3 | | 2=2n |